Dabrafenib plus trametinib in elderly patients (>75 years) with BRAF V600E mutated metastatic non-small-cell lung cancer: A multicenter retrospective experience from real-life. Issue 1 (2022) - Maione, P; Marinis, F; Romano, G; Spitaleri, G; Galetta, D; Morabito, A; Rocco, D; Tiseo, M
No abstract available